Analisis Faktor Penyebab Stres Akademik Mahasiswa Tingkat Akhir dan Upaya Mengatasinya Perspektif Teori Psikososial Erik Erikson - Ali Uroidli; Andry Syahrul Prayoga; Siti Khorriyatul Khotimah (IDEA: Jurnal Psikologi, 2024)
This study aims to analyze the factors that cause academic stress in final year students and design coping strategies using Erik Erikson's Psychosocial theory approach. The research method used is mixed quantitative and qualitative research with a case study approach at UIN Sunan Ampel Surabaya. Data collection was carried out through participatory observation, in-depth interviews, and online questionnaires filled out by 20 respondents of final year students of the Master of Islamic Education Study Program. Data analysis was conducted using multiple linear regression for quantitative data and Miles and Huberman data analysis for qualitative data. The results showed that self-motivation has a significant influence on academic stress levels (p < 0.05), although campus environment factors, workload, and family conditions also have an important role with an overall total of 80.7%. Support from relevant institutions such as universities and the government is considered important in overcoming academic stress, by providing counseling services, mental well-being programs, time management training, and social activities. By creating a supportive environment, it is expected that students can feel more motivated and able to manage academic stress better.